2009
DOI: 10.1200/jco.2009.27.18_suppl.cra506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of omission of completion axillary lymph node dissection (cALND) or axillary radiotherapy (ax RT) in breast cancer patients with micrometastases (pN1mi) or isolated tumor cells (pN0[i+]) in the sentinel lymph node (SN): Results from the MIRROR study

Abstract: CRA506 Background: The Dutch MIRROR study is the largest cohort study on pN1mi and pN0(i+) in the SN era with long-term follow-up, central pathology review (6th AJCC-classification), and separate analyses on the use of adjuvant systemic therapy (AST). In patients not receiving AST, pN1mi and pN0(i+) as final N-stage were shown to be independent prognosticators for disease-free survival (SABCS 2008, #23, oral). As a substantial number of patients in the MIRROR study did not undergo cALND or ax RT, we questione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…As reported in the previous studies, the low identification rate of micrometastases by frozen section and conventional H&E staining (7) and the strong evidence about the impact of micrometastatic nodal disease on locoregional recurrence (31,32) warrant identification of primary tumour-related histopathological factors with high predictive ability. Many studies have validated the MSKCC nomogram, which was proposed for predicting non-SLN metastases.…”
Section: Resultsmentioning
confidence: 87%
“…As reported in the previous studies, the low identification rate of micrometastases by frozen section and conventional H&E staining (7) and the strong evidence about the impact of micrometastatic nodal disease on locoregional recurrence (31,32) warrant identification of primary tumour-related histopathological factors with high predictive ability. Many studies have validated the MSKCC nomogram, which was proposed for predicting non-SLN metastases.…”
Section: Resultsmentioning
confidence: 87%
“…Invasive lobular 4 (13) 21 (13) 13 (20) 6 (15) 5 (25) Select studies of patients with positive SLN and who did not undergo ALND have demonstrated low regional recurrence rates in the setting of adjuvant systemic therapy and RT (Table 5). 1,[5][6][7][8][9][10][11][12][13][14]28 Those series differed with respect to the length of median follow-up, the definition of a positive SLN, reasons for omitting ALND, and the receipt of systemic therapy. Although several of those reports 1,5,7,11 described the RT fields used, none reported treatment outcomes stratified by RT field design.…”
Section: Discussionmentioning
confidence: 99%
“…Omission of any axillary treatment resulted in a higher 5-year recurrence rate in pN1(mi) but not in pN0(i+) patients (5% vs. 1%, hazard ratio (HR) 4.39) [28], even after correction for adjuvant systemic treatment.…”
Section: Slnb and Low-volume Metastatic Involvementimplications For Aldmentioning
confidence: 94%